An Accented Cinema : Exilic and Diasporic Filmmaking - Naficy, Hamid (Book collections on Project MUSE., 2001)
An overview of the filmmaking of postcolonial, Third World, and other displaced individuals living in the West. How their personal experiences of exile or diaspora translate into cinema is a key focus of the text. The text presents comprehensive and global coverage of this genre.